On Second Chances and Stratification: How Sociologists Think About Community Colleges. (January 2015) - Schudde, Lauren; Goldrick-Rab, Sara
Community colleges increase college access, extending postsecondary educational opportunities to underserved students, yet, these students exhibit low rates of program completion and transfer to 4-year colleges. Sociological research on community colleges focuses on the tension between increasing educational opportunity and failing to improve equity in college completion across key demographics, such as race and socioeconomic status. This article provides an overview of sociology's approach to understanding community colleges. We describe sociological theories, examine the contributions they make to the field, and discuss the discipline's recent debates regarding community colleges. We conclude by highlighting research areas for further progress and discussing the role sociology could play in transforming community colleges.